2020
DOI: 10.3390/curroncol28010020
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing Alloderm-RTU with DermACELL in Immediate Subpectoral Implant-Based Breast Reconstruction

Abstract: Background: The effectiveness of different acellular dermal matrices (ADM) used for implant-based reconstruction immediately following mastectomy is an important clinical question. A prospective randomized clinical trial was performed to evaluate the superiority of DermACELL over Alloderm-RTU in reducing drain duration. Methods: Patients undergoing mastectomy with subpectoral immediate and permanent implant-based breast reconstruction were randomized to Alloderm-RTU or DermACELL. The primary outcome was seroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 40 publications
(31 reference statements)
1
19
0
Order By: Relevance
“…Previous studies have shown relatively lower complication rates of sterile pre-hydrated ADMs compared with other aseptic or/and freeze-dried ones (17,23,24). Conversely, there is increasing evidence that no statistically significant differences were observed between sterile versus aseptic ADMs in drain duration and complications after IBR (16,18,25,26). In this study, the results indicate that CGCRYODERM has a safety profile comparable with that of DermACELL.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown relatively lower complication rates of sterile pre-hydrated ADMs compared with other aseptic or/and freeze-dried ones (17,23,24). Conversely, there is increasing evidence that no statistically significant differences were observed between sterile versus aseptic ADMs in drain duration and complications after IBR (16,18,25,26). In this study, the results indicate that CGCRYODERM has a safety profile comparable with that of DermACELL.…”
Section: Discussionmentioning
confidence: 98%
“…13 AlloDerm (Allergan Inc., Madison, NJ), DermACELL (LifeNet Health, Virginia Beach, VA), and Graftjacket (Wright Medical Group N.V., Memphis, TN) are three popular human-derived ADMs that provide nonliving dermal scaffolding of collagen, elastin, and glycosaminoglycans to open wound beds to promote healing. 14 The long shelf lives and increased supply compared with skin grafting have made these acellular dermal allografts a popular choice for wound coverage. Further, they provide a barrier against infection, help decrease fluid losses, and provide a more favorable wound bed for future skin grafting.…”
Section: Acellular Skin Substitutesmentioning
confidence: 99%
“…17 AlloDerm requires 10 to 14 minutes of rehydration prior to application; however, the Ready-To-Use product only requires 2 minutes of rehydration. 14 AlloDerm grafts have been shown to be tolerant to infection and revascularize quickly. 14 DermACELL, in comparison, can also be stored at room temperature, but it is ready to use directly out of the package.…”
Section: Acellular Skin Substitutesmentioning
confidence: 99%
See 2 more Smart Citations